Akuntabilitas Pengelolaan Perpuluhan Jemaat - Patty, Agustina Christina; Kwalomine, Azmida L.; Gomies, Stevanus Johan (Journal of Business Application, 2023)
This study was aimed to understand the meaning of by-tens accountability in GPM BETHEL Church. By thents accountability is a phenomenon that should be examined by the church. Paradigm used in this study was interpretive paradigm with Husserl transcendental phenomenology”. Based on meaningful accountability practice, thus BETHEL Church Congregation of Allang had three accountability dimension that are: social dimension which put by tenth accountability being understand as self-responsibility toward church and social responsibility toward people in need. and finance dimension which is a supporting dimension between spiritual and social dimension. BETHEL Church Congregation of Allang actually had long-practice accountability.